Nitroimidazole-Induced Reversible Neurotoxicity - Dinesh Chouksey; Amandeep Singh; Nitisha Goyal; Ajoy K. Sodani (Indian Journal of Medical Specialities)
The nitroimidazole group of drugs is commonly used in India and worldwide for diarrhea and other indications. People are taking it over the counter for their subsequent problems without consultation, and this is harmful to them on chronic use. Similarly, many indications such as amoebic liver abscess need long-duration therapy of these drugs which may present with its toxic effects. We report two cases of metronidazole and ornidazole overuse presented as central and peripheral nervous system toxicity. The magnetic resonance imaging changes similar to nitroimidazole drug toxicity can be seen in many other diseases, and it needs to correlate with a good history for the diagnosis to avoid unnecessary workup burden to the patient.